Long-term health effects of outdoor air pollution on asthma and respiratory symptoms among adults in low-and middle-income countries (LMICs): a systematic review and meta-analysis - Abbah, Achenyo Peace; Xu, Shanshan; Johannessen, Ane (Frontiers in Environmental Health, 2024)
Background: Few studies have investigated the association between long-term exposure to outdoor air pollution and the risk of asthma and respiratory symptoms in low-and middle-income countries (LMICs).Objective: To systematically evaluate the epidemiological evidence regarding the associations between long-term exposure to outdoor air pollution and respiratory symptoms in LMICs.We searched for literature published between January 1946 and September 2022 We searched for literature up to September 2022 in Embase (Ovid), Medline (Ovid), and Web of Science (Core Collection). The air and gaseous pollutants studied included particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), and black carbon (BC), and exposure was 1-year duration or more. We conducted a systematic review and meta-analysis with a random-effects model to calculate the relative risk (RR) estimates. A rerun of the databases was conducted in November 2023 with no eligible studies found.Of the 1346 studies identified, only six met our inclusion criteria, and these six reported PM2.5, PM10, and NO2 with asthma as the main outcome. Three of these included studies were further included in the meta-analysis because they had data on the same exposure and outcome (PM2.5 and asthma). The main result of our study showed a borderline significant association between a 10 µg/m 3 increase in exposure to PM2.5 and an increased risk of asthma (RR 1.21, 95% CI 0.93, 1.50). There was evidence of considerable heterogeneity (I 2 =75.87%). The regressionbased Egger test for small-study effects showed no significant publication bias among these three studies.Our results indicate that long-term exposure to PM2.5 increases the risk of asthma in LMICs, but studies are scarce and there is a large need for more research in LMICs in this field.